Social Studies Thematic Learning Difficulty Analysis Through Microsoft Teams - Suyanti, Suyanti; Ariyanto, Eka Nofri (Journal of Learning Improvement and Lesson Study, 2023)
This research is a qualitative research with a case study approach about the difficulty of learning online-based thematic social studies through the Microsoft Teams application for fourth grade students of SDN 02 Pangongangan. The purpose of this study was to determine the factors that cause students to have difficulty learning thematic through the Microsoft Teams application for grade IV students of SDN 02 Pangongangan. The data collection techniques used are observation, interview, and documentation. The results of this study can be stated as follows: (a) in the process of thematic learning through the Microsoft Teams application, it can run well; (b) factors that influence the difficulty of learning thematic through the Microsoft Teams application are internal factors which include students’ intellectual abilities, student interests, student motivation and external factors which include learning media, school facilities and infrastructure and family environmental conditions; (c) solutions offered by researchers include applying interesting and varied methods and learning, applying more varied learning media and increasing the preparation of learning tools more optimally, especially in thematic learning.